HALL-MOBILITY AND TEMPERATURE-DEPENDENT PHOTOLUMINESCENCE OF CARBON-DOPED GAAS - KIM, SI; KIM, Y; LEE, MS; KIM, MS; MIN, SK; LEE, CC (PERGAMON-ELSEVIER SCIENCE LTD, 1993)
We have analyzed Hall mobilities and photoluminescence (PL) spectra of carbon(C)-doped GaAs epilayers as a function of hole concentration and temperature. We have obtained an empirical relation of hole concentration dependent Hall mobility appropriate for C-doped GaAs which have higher Hall mobilities than Zn-doped GaAs. By PL measurement, temperature dependence of band gap energy E(g) and PL peak energy E(M) shift of C-doped GaAs with a hole concentration of 9.2 x 10(19) cm(-3) have been measured. The resulting E(g) and E(M) at 0 K are (1.420 +/- 0.003) eV and (1.458 +/- 0.003) eV, respectively. The PL peak energy of C-doped GaAs with hole concentrations varying from 1 x 10(17) to 9.2 x 10(19) cm(-3) have been measured and compared with previously reported data.